ASSOCIATION OF EXPRESSION OF NFKB1, HIF1, VEGFA, VEGFВ, BAX, BCL2 GENES WITH BIOCHEMICAL REMEDIATION IN PATIENTS WITH LOCALIZED PROSTATE CANCER - Ph. S. Bova; O. I. Kit; A. Yu. Maksimov (Исследования и практика в медицине, 2019)
Aim. To identify the association of NFKB1, HIF1, VEGFA, VEGFB, BAX, BCL2 gene expression in prostate adenocarcinoma cells with biochemical recurrence of localized prostate cancer.Patients and methods. Three groups of patients were formed in the study – the main one, the comparison group and the control group. In patients with prostate cancer (PC) in the main group (n = 56) with biochemical recurrence (BR) for two years after radical surgery, as well as in 60 patients without BR (experimental group) by real-time PCR in prostate cancer tissue the expression of genes NFKB1, HIF1, VEGFA, VEGFВ, BAX, BCL2 was determined. The control group consisted of 55 patients in whom, when performing diagnostic punctures for benign prostate tumors, biopsy specimens were taken in healthy tissues. The age of patients in the three groups ranged from 57 to 74 years (median 63 years). When quantifying expression of genes NFKB1, HIF1, VEGFA, VEGFВ, BAX, BCL2, the difference in the values of reaction threshold cycles (Ct) fixed for the studied and reference genes was determined. The relative level (Expr) was the ratio of Ct medians for each gene in two compared groups of the studied three ones: in the main group to the indicator in the control group, in the experimental group to the indicator in the control group, and also between the main group and the experimental group.Results. A comparative analysis of gene expression in prostate cancer tissue in the main group compared with the experimental group showed a statistically significant increase (p < 0,05) in the relative index for the HIF1 gene (2,7 times), the VEGFA gene (2,4 times ) and the NFKB1 gene (2 times). Consequently, in patients with localized early recurrence prostate cancer, initially in the prostate tissue, a higher level of expression of the NFKB1, HIF1 and VEGFA genes was established. In the experimental group relative to the control group, the expression of the proapoptic gene BAX was 1,6 times higher (p < 0,05), and for the antiapoptic gene BCL2 no changes were detected (p = 0,09). Thus, in patients with localized prostate cancer in the absence of BR, after radical prostatectomy, an initial increase in the expression of the BAX gene promoted the activation of apoptosis. In patients with localized prostate cancer, subsequent biochemical recurrence initially in the tissue of prostate adenocarcinoma inhibition of apoptosis due to increased expression of the BCL2 gene was observed.Conclusion. Enhancement of NFKB1, VEGFA, HIF1 and BCL2 gene expression in prostate tissue is associated with the development of BR in patients with localized prostate cancer.